The Recent Convergence of Financial Development in Asia. Issue 5 (3rd May 2016) - Dekle, Robert; Pundit, Madhavi
ABSTRACT: We construct an index of financial development for twenty-three Asian economies based on sub-indices of access, depth, and efficiency of financial institutions and markets and find evidence that economies with weaker financial systems are catching up to the Asian benchmark economies, namely Hong Kong, China; Japan; the Republic of Korea; and Singapore. Gross domestic product (GDP) per capita, aggregate GDP, and mobile subscriptions all increase the growth rate of financial development in Asian economies while institutional factors have insignificant or ambiguous effects. We also evaluate the relative importance of the sub-indices in delivering high economic growth, low volatility, and greater financial access.